2022
DOI: 10.3390/jof8070727
|View full text |Cite
|
Sign up to set email alerts
|

Postantifungal Effect of Antifungal Drugs against Candida: What Do We Know and How Can We Apply This Knowledge in the Clinical Setting?

Abstract: The study of the pharmacological properties of an antifungal agent integrates the drug pharmacokinetics, the fungal growth inhibition, the fungicidal effect and the postantifungal activity, laying the basis to guide optimal dosing regimen selection. The current manuscript reviews concepts regarding the postantifungal effect (PAFE) of the main classes of drugs used to treat Candida infections or candidiasis. The existence of PAFE and its magnitude are highly dependent on both the fungal species and the class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Nystatin appeared effectiveness against yeasts and anthropophilic dermatophytes, Goldstein and Beth [36] mentioned previously that nystatin is effective for cutaneous candidiasis but not for the treatment of dermatophytes, however it was effective for T. rubrum in present study; therefore, treatments with antifungals require a sensitivity test at laboratory of mycology to get the suitable antifungal and dose for the patients [37].…”
Section: Activity Of Antifungal Agentsmentioning
confidence: 53%
“…Nystatin appeared effectiveness against yeasts and anthropophilic dermatophytes, Goldstein and Beth [36] mentioned previously that nystatin is effective for cutaneous candidiasis but not for the treatment of dermatophytes, however it was effective for T. rubrum in present study; therefore, treatments with antifungals require a sensitivity test at laboratory of mycology to get the suitable antifungal and dose for the patients [37].…”
Section: Activity Of Antifungal Agentsmentioning
confidence: 53%
“…The potential of drug interactions is negligible as well as the risk of resistance selection. It has concentration-dependent fungicidal activity, a prolonged half-life and showed an extended post-antifungal effect in time-kill studies [226]. Moreover, due to the lipophilic characteristics, it might be less affected by pathophysiological changes than hydrophilic drugs like echinocandins.…”
Section: In Patients With Septic Shock and Multi-organ Failure Empiri...mentioning
confidence: 99%
“…This standardized procedure was adopted in other experiments where changes were applied only to incubation time after disposal of the fungal suspension on solid medium according to the species-specific time of growth [113,114]. Results from multiple studies conducted on PAFE showed that this phenomenon was largely influenced by the species, the class of molecule, as AMB and echinocandin showed prolonged inhibition of growth after removal, and drug concentration, as higher PAFE was registered with higher antifungal concentrations [114,115].…”
Section: Microbiological and Pharmacological Factors Altering Interpr...mentioning
confidence: 99%
“…From a clinical and pharmacological standpoint, PAFE influences the timing of antifungal drug administration, with drugs with prolonged PAFE requiring a lower dosing per day [111,115]. On the other hand, PAFE-induced prolonged inhibition of growth might alter the results of fungicidal in vitro tests, as microorganisms whose growth was only PAFE-inhibited were not actually killed.…”
Section: Microbiological and Pharmacological Factors Altering Interpr...mentioning
confidence: 99%